A qualitative content analysis: the type of animation and elements of nationalism used in animation series of Upin & Ipin in episodes: Magic Pimpimpong, Masih Ada Sayang & Kompang Dipalu / Noor Ashikin Seman, Noor Nirwandy Mat Noordin and Fariza Hanis Abdul Razak - Seman, Noor Ashikin; Mat Noordin, Noor Nirwandy; Abdul Razak, Fariza Hanis (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2018)
The results of this study provide the insights of nationalism elements and the type of animation that brings the nationalism's spirit among viewers. The study investigates the elements of nationalism that were used in the animation series of Upin & Ipin through episodes: Magic Pimpimpong, Masih Ada Sayang, and Kompang Dipalu. Viewers learn the subliminal messages conveyed through elements of nationalism with the aimed at boosting their nationalism spirit. The study uses qualitative content analysis method by encoding all three episodes of Upin & Ipin animated series into a table. In order to capture every scene, Video Content Analysis (VCA) was used as a research instrument to record all important images. The coding table is classified into several elements of nationalism and is coded accordingly. The results of the analysis show that the type of animation and the elements of nationalism play an important role in capturing images and symbols to improve nationalism spirits in younger generations. The results also suggest that viewers need to pay more attention in order to receive the subliminal messages of nationalism in the animation series of Upin & Ipin.